Analisis Pornografi Balas Dendam (Revenge Porn) dan Regulasinya di Indonesia - Alfira Destriannisya (Indonesian Journal Publisher, 2024)
This study delves into the pervasive issue of revenge porn, a form of online-based gender crime facilitated by the rapid advancements in digital technology. Revenge porn entails the non-consensual dissemination of sexual content, posing significant risks and harm to its victims. The research aims to elucidate the potential impacts of revenge porn on its victims and explore the existing legal protections available to them. Employing both normative and empirical juridical methods, the study draws upon literature review to uncover the psychological and sociological ramifications endured by victims, which often manifest in detrimental physical effects. Despite the absence of comprehensive legal safeguards specifically addressing online-based sexual violence and revenge porn in Indonesia, existing legal provisions, such as those outlined in Law Number 44 of 2008 concerning Pornography and Law Number 19 of 2016 concerning Electronic Information and Transactions, offer a semblance of protection for victims. Through a thorough examination of these legal frameworks, this research underscores the urgent need for robust legal measures to safeguard individuals from the perils of online-based gender crimes, particularly revenge porn.